2005
DOI: 10.1677/joe.1.06264
|View full text |Cite
|
Sign up to set email alerts
|

Is dehydroepiandrosterone a hormone?

Abstract: Dehydroepiandrosterone (DHEA) is not a hormone but it is a very important prohormone secreted in large amounts by the adrenals in humans and other primates, but not in lower species. It is secreted in larger quantities than cortisol and is present in the blood at concentrations only second to cholesterol. All the enzymes required to transform DHEA into androgens and/or estrogens are expressed in a cellspecific manner in a large series of peripheral target tissues, thus permitting all androgen-sensitive and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(261 citation statements)
references
References 254 publications
7
246
2
6
Order By: Relevance
“…We could speculate that the higher basal levels of DHEA in WL might be related to the greater social tolerance shown by WL females [53]. To our knowledge this is the first study which clearly shows that short term stress causes a decrease of blood DHEA levels in any avian breed, and in most species the circulating levels are very low [54].…”
Section: Discussionmentioning
confidence: 71%
“…We could speculate that the higher basal levels of DHEA in WL might be related to the greater social tolerance shown by WL females [53]. To our knowledge this is the first study which clearly shows that short term stress causes a decrease of blood DHEA levels in any avian breed, and in most species the circulating levels are very low [54].…”
Section: Discussionmentioning
confidence: 71%
“…The underlying mechanisms are presently uncertain; MacLusky et al (2006) point to a varety of possibilities that might be exploited clinically. DHEA, considered a "weak" androgen, also increases spine synaptic density (Parducz et al, 2006) but as shown by Labrie (2005) and others, can be aromatized to estradiol.…”
Section: Androgensmentioning
confidence: 96%
“…The adrenal secretes dihydroepiandosterone (DHEA) which acts on peripheral tissues such as the mammary gland and prostrate. DHEA begins to fall steeply during middle age (Labrie et al 2001(Labrie et al ,2005. Such changes evoke questions about how measures of reduced androgen function such as diminished circulating free testosterone, might promote Alzheimer's disease (Hogervorst et al, 2004;Moffat et al, 2004).…”
Section: Androgensmentioning
confidence: 99%
“…Dehydroepiandrosterone-sulfate (DHEA-S), a derivative of dehydroepiandrosterone, is also an adrenal steroid. Unlike cortisol, DHEA-S is not a hormone itself, but rather an important prohormone, meaning that it is a substance that converts to other hormones (Labrie et al, 2005). Specifically, DHEA-S is a precursor to androstenedione, testosterone, and estrogens in adolescents and adults (Labrie, Luu-The, Labrie, & Simard, 2001).…”
Section: Affectionate Communicationmentioning
confidence: 99%